Dividend Policy and Share Price Volatility: Evidence from Companies Listed in Indonesia Stock Exchange - Laksana Sadewo, Puger B1024151015 (Jurnal Manajemen Update, 2019)
This study analyzed the importance of dividend policy which has been attracting shareholders’ attention as it might determine the return that they could earn. On the other hand, investors might have differences in their investing decision, mainly to their preference toward how volatile the company’s shares price. Share price volatility (SPV) is used as dependent variable, while the independent variables of dividend policy are measured by dividend yield (DY), dividend payout ratio (DPR), assets growth (AG), leverage (LV), firm’s size (FS), and earnings volatility (EV). The data are estimated by using regression on panel data EGLS (cross-section weight) with the basis of Fixed Effect Model. The result indicates a mixed result. Dividend yield and dividend payout ratio have a positive effect toward share price volatility, although only dividend payout ratio which has significant impact. In addition, firm’s size and earnings volatility show a positive relationship with share price volatility as well. On the other hand, firm leverage has a negative influence on share price volatility. Lastly, assets growth and share price volatility do not have a significant relationship.Allen, D. E., & Rachim, V. S. (1996). Dividend Policy and Stock Price Volatility: Australian Evidence. Applied Financial Economics, 6(2), 175-188.Al-Malkawi, H. N. (2007). Determinants of Corporate Dividend Policy in Jordan. Journal of Applied Accounting Research, 23, 44-70.Amihud, Y., & Murgia, M. (1997). Dividends, Taxes, and Signaling: Evidence from Germany. Journal of Finance, 397-408.Asghar, M., Ali Shah, S. Z., Hamid, K., & Suleman, M. T. (2011). Impact of Dividend Policy on Stock Price Risk: Empirical Evidence from Equity Market of Pakistan. Far East Journal of Psychology and Business, 4.Asquith, P., & Mullins Jr, D. W. (1983). The Impact of Initiating Dividend Payment on Shareholders' Wealth. Journal of Business, 77-96.Baltagi, B. (2005). Econometric Analysis of Panel Data. John Wiley & Sons.Baskin, J. (1989). Dividend Policy and The Volatility of Common Stock. Journal of Portfolio Management, 15, 19-25.Black, F. (1976). The Dividend Puzzle. Journal of Portfolio Management, 2, 5-8.Black, F., & Scholes, M. (1974). The Effect of Dividend Yield and Dividend Policy on Common Stock Prices and Returns. Journal of Financial Economics, 1(1), 1-22.Brama, A. (2018). Negara Terima Dividend Lebih Tinggi Daripada Tahun Lalu. Jakarta: investasi.kontan.co.id.Brennan, M. (1971). A Note on Dividend Irrelevance and the Gordon Valuation Model. The Journal of Finance, 26(5), 1115-1121.Carpi, A., & Egger, A. E. (2009). Controlling Variables. Retrieved 1 12, 2016Creswell, J. W. (2003). Research Design Qualitative, Quantitative, and Mixed Methods Approach Second Edition. United States: Sage Publications.Diamond, J. J. (1967). Earnings Distribution and Evaluation of Shares: Some Recent Evidence. Journal of Financial and Quantitative Analysis, 2, 15-30.Gitman, L. J. (2006). Principles of Managerial Finance (11th ed.). Boston: Pearson Addison Wesley.Gitman, L. J., & Zutter, C. J. (2012). Principle of Managerial Finance 13th Edition. United States: Pearson.Gordon, M. J. (1959). Dividends, Earning, and Stock Prices. Review of Economics and Statistics, 2, 99-105.Green, W. H. (2003). Econometrics Analysis 5th Edition. New Jersey: Prentice Hall.Gujarati, D. (2003). Basic Econometric Fourth Edition (4 ed.). New York: McGraw-Hill.Habib, Kiani, & Khan. (2012). Dividend Policy and Share Price Volatility: Evidence from Pakistan. Global Journal of Management and Business Research, 12(5)Harmono. (2011). Manajemen Keuangan  Berbasis Balanced Scorecard Pendekatan Teori, Kasus, dan Riset Bisnis (Edisi 1). Jakarta:Bumi Aksara.Hashemijoo, M., Ardekani, A. M., & Younesi, N. (2012). The Impact of Dividend Policy on Share Price Volatility in the Malaysian Stock Market. Journal of Business Studies Quarterly, 4, 111-129.Holder, M. E., Langrehr, F., & HExter, J. L. (1998). Dividend Policy Determinants: An Investigation of the Influences of Stakeholder Theory. Financial Management, 73-82.Hooi, Albaity dan Ibrahimy.(2015). Dividen Policy and Share Price Volatility.Investment Management and Financial Innovations, 12.Hussainey, K., Mgbame, C. O., & Chijoke-Mgbame, A. M. (2011). Dividend Policy and Share Price Volatility: UK Evidence. Journal of Risk Finance, 12, 57-68.Hyde, K. (2000). Recognising Deductive Processes in Qualitative Research. Qualitative Market Research: An International Journal, 3, 82-89.Ilaboya, O. J dan M. Aggreh.(2013). Dividend Policy and Share Price Volatility.J. Asian Dev.Stud, 2(2).Jensen, G. R., Solberg, D. P., & Zorn, T. S. (1992). Simultaneous Determination of Insider Ownership, Debt, and Dividend Policies. Journal of Financial and Quantitative Analysis, 27, 247-263.Jo, H., & Pan, C. (2009). Why are Firms with Entrenched Managers More Likely to Pay Dividends? Review of Accounting and Finance, 8(1), 87-116.Kyle A, Profilet dan Frank W, Bacon. (2013). Dividend Policy and Stock Price Volatility in The U.S Equity Capital Market. Proceedings of ASBBS, 20(1).Lewellen, W. G., Stanley, K. L., Lease, R. C., & Schlarbaum, G. G. (1978). Some Direct Evidence on the Dividend Clientele Phenomenon. The Journal of Finance, 33, 1385-1399.Lind, D. A., Marchal, W. G., & Wathen, S. A. (2004). Statistical Techniques in Business & Economics (12th ed.). New York: McGraw-Hill/Irwin.McManus, P. A. (2011). Introduction to Regression Model for Panel Data Analysis.Miller, M. H., & Modigliani, F. (1961). Dividend Policy, Growth, and The Valuation of Shares. The Journal of Business, 34, 411-433.Myers, S. C., & Majluf, N. S. (1984). Corporate Financing and Investment Decisions When have Information the Investors do not Have. Journal of Financial Economics 13, 187-221.Nachrowi, N. D., & Usman, H. (2002). Penggunaan Teknik Ekonometri. Jakarta: PT RajaGrafindo Persada.Nachrowi, N. D., & Usman, H. (2006). Pendekatan Populer dan Praktis Ekonometrika untuk Analisis Ekonomi dan Keuangan. Jakarta: LPFE Universitas Indonesia.Nazir, M. S., Nawaz, M. M., Anwar, W., & Ahmed, F. (2010). Determinants of Stock Price Volatility in Karachi Stock Exchange: The Mediating Role of Corporate Dividend Policy. International Research Journal of Finance and Economics(55).Newbold, P., Carlson, W. L., & Thorne, B. M. (2003). Statistics for Business and Economics (5th ed.). New Jersey: Pearson Education.Ngoc, Dinh Bao dan Cuong, Nguyen chi. (2016).Impacts of Cash Dividend Policy on Stock Price Volatility.Proceedings of 11th Annual London Business Research Conference.Imperial College, London, UK.Park, H. M. (2008). Linear Regression Models for Panel Data Using SAS, STATA, LIMDEP, and SPSS. Indiana: The Trustees of Indiana University.Pettit, R. R. (1972). Dividend Announcements, Security Performance, and Capital Market Efficiency. Journal of Finance, 27, 993-1007.Pettit, R. R. (1977). Taxes, Transaction Costs, and the Clientele Effect of Dividends. Journal of Financial Economics, 5, 419-436.Pettit, R., & Singer, R. (1985). Small Business Finance: A Research Agenda. Financial Management, Vol. 14 No. 3, 47-60.Rashid, A., & Rahman, A. A. (2007). Dividend Policy and Stock Price Volatility: Evidence from Bangladesh. Journal of Applied Business and Economics.Roll, R. (1988). R2. Journal of Finance, 43(3), 540-566.Santioso, Linda, & Angesti, Yosevin Gloria. (2019). Faktor-Faktor Yang Mempengaruhi Volatilitas Harga Saham Perusahaan Manufaktur. Jurnal Ekonomi, Vol. XXIV, No. 01, 46-64Saunders, M., Lewis, P., & Thornhill, A. (2009). Research Methods for Business Students (5th ed.). England: Pearson Education.Saxena, A. K. (1999). Determinants of Dividend Payout Policy: Regulated versus Unregulated Firms. Journal of Applied Topics in Business and Economics.Schloz, J. K. (1992). A Direct Examination of the Dividend Clientele Hypothesis. Journal of Public Economics, 49, 261-285.Shah, S. A., & Noreen, U. (2016). Stock Price Volatility and Role of Dividend Policy: Empirical Evidence from Pakistan. International Journal of Economics and Financial Issues, 6, 461-472.Sadiq, Ahmad, Anjum, dan Rehman. (2013). Stock Price Volatility in Relation to Dividend Policy : A Case Study of Karachi Stock Market. Middle-East Journal of Scientific Research.1(1).Shiller, R. J. (1987). The Volatility of Stock Market Prices. Science, New Series, 235, 33-37.Stephen, Gregory dan Maurice. (2015). Effect of Dividend on Share Price Volatility in Frontier Exchanges : Kenya’s Perspective. Research Journal of Finance and Accounting, 6.Sugiyono. (2011). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung.Travlos, N., Trigeorgis, L., & Vafeas, N. (2001). Shareholder Wealth Effects of Dividend Policy Changes in an Emerging Stock Market. Multinational Finance Journal, 5, 87-112.Theresia, Priskilla & Arilyn, Erika Jimena (2015). Pengaruh Dividen, Ukuran Perusahaan, Hutang Jangka Panjang, Earning Volatility, Pertumbuhan Aset, Trading Volume, dan Volatilitas Harga Saham. Jurnal Bisnis dan Akuntansi, 17(2).Trigueiros, D. (2000). A Theoritical Definition and Statistical Description of Firm Size. Writing Paper, 1-25.Uddin, M. H., & Chowdhury, G. M. (2005). Effect of Dividend Announcement on Shareholders Value: Evidence from Dhaka Stock Exchange. Journal of Business Research.Widarjono, A. (2007). Teori dan Aplikasi Untuk Ekonomi dan Bisnis. Yogyakarta: Ekonosia FE Universitas Islam Indonesia.William, R. (2015). Panel Data 4: Fixed vs Random Effects Models. Indiana.Zakaria, Z., Muhammad, J., & Zulkifli, A. H. (2012). The Impact of Dividend Policy on the Share Price Volatility: Malaysian Construction and Material Companies. Internationa Journal of Economics and Management Sciences, 2(5), 1-8.Zikmund, W. G., Babin, B. J., Carr, J. C., & Griffin, M. (2010). Business Research Methods (8th ed.). United States: South-Western College.